1998
DOI: 10.1108/01425459810238800
|View full text |Cite
|
Sign up to set email alerts
|

Functional flexibility: merely reacting or acting strategically?

Abstract: Functional flexibility 505 strong, temporary team structures gain in importance, starting with the trend that a falling share of jobs can be completely formalised and thus electronically automated, while on the other hand the share of jobs with a high degree of complexity is constantly growing (Ruf, 1991, p. 30). This development has clear repercussions for the company's hierachical structure, the company's internal formalism, the specific communicational structure, and also the spatial and temporal dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 17 publications
2
28
0
6
Order By: Relevance
“…Due to the rapid process of knowledge obsolescence in current environments, the importance of being "ahead on the learning curve" is crucial in creating flexible employees (Dyer & Shafer, 2002). Extensive developmental activities in the HPWS are likely to favor the abilities needed to perform a variety of tasks effectively, namely, to promote functional flexibility (Friedrich, Kabst, Weber, & Rodehuth, 1998;van Dam & Thierry, 2000). In addition, the focus of HPWS on the workforce's development provides a firm with a skilled workforce capable of ongoing learning (Batt, 2002;Youndt & Snell, 2004).…”
Section: Hpws-hr Flexibility Relationshipmentioning
confidence: 99%
“…Due to the rapid process of knowledge obsolescence in current environments, the importance of being "ahead on the learning curve" is crucial in creating flexible employees (Dyer & Shafer, 2002). Extensive developmental activities in the HPWS are likely to favor the abilities needed to perform a variety of tasks effectively, namely, to promote functional flexibility (Friedrich, Kabst, Weber, & Rodehuth, 1998;van Dam & Thierry, 2000). In addition, the focus of HPWS on the workforce's development provides a firm with a skilled workforce capable of ongoing learning (Batt, 2002;Youndt & Snell, 2004).…”
Section: Hpws-hr Flexibility Relationshipmentioning
confidence: 99%
“…Skinner (1999), Sly et al, (1998) and Friedrich et al, (1998) found that efficiency and flexibility play an important role in the organization to achieve its objectives. Comments on the management of Islamic institutions in Malaysia about incompetence, sluggishness, and delays in service delivery by IAM are often revealed by the mainstream media (Rumaizuddin et al, 2011).…”
Section: Lack Of Trainingmentioning
confidence: 99%
“…As Cordery et al (1993) and Friedrich et al (1998) suggest, these job enrichment activities increase the skill repertoire of employees and consequently, their functional flexibility. Furthermore, these activities can foster employee functional flexibility through motivation, since enriched jobs may lead to a more satisfied workforce that is more willing to be flexible (Van den Berg & Van der Velde, 2005).…”
Section: Qm and Internal Labour Flexibilitymentioning
confidence: 99%
“…The service sector provides an appropriate field to study labour flexibility due to the high levels of variability and heterogeneity that characterise services. In addition, certain studies such as that of Friedrich et al (1998) have observed different trends in manufacturing and service sectors with regard to functional and external flexibility. By limiting our analysis to service sectors we are able to avoid confounding influences.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation